Math, asked by gcvjj, 4 months ago

Help to prove this pls​

Attachments:

Answers

Answered by susobhanakhuli8537
0

Answer:

2cosecA

Step-by-step explanation:

\frac{1}{cosecA-cotA} +\frac{1}{cosecA+cotA} = \frac{(cosecA + cotA)+(cosecA-cotA)}{cosec^{2}A-cot^{2}A  }  

                                        = \frac{2cosecA}{1}         [∵ cosec^{2}A-cot^{2}A =1]

                                        = 2cosecA

Answered by pihu4976
0

Answer:

Hope it helps you!!!!!!

Attachments:
Similar questions